Does a cute artificial intelligence assistant soften the blow? The impact of cuteness on customer tolerance of assistant service failure. (March 2021) - Lv, Xingyang; Liu, Yue; Luo, Jingjing; Liu, Yuqing; Li, Chunxiao
Abstract: As artificial intelligent technologies have been increasingly applied in tourism and hospitality industry, the service failure caused by artificial intelligence assistant and how to recover them are worth empirical studying. Laboratory experiments were employed to test the impact of cuteness in service failure, with effective manipulation of cute appearance, cute voice and cute language style of artificial intelligence assistant. By utilizing three studies with seven experiments, this research demonstrated the positive effect of cuteness design of artificial intelligence assistant on customer tolerance of service failure and further revealed the two mediating paths (tenderness and performance expectancy) as well as the boundary (failure severity and time pressure) of the cuteness effect. These findings contribute to the knowledge on artificial intelligent assistant service and provide insight for cute design using in tourism and hospitality industry. Graphical abstract: Unlabelled Image Highlights: Cuteness design of AI assistant influences customers' tolerance of service failure. Seven experiments were used to examine the cuteness effect and the mechanism behind. Cuteness can be designed through appearance, voice or language style. Cuteness effect was mediated by tenderness and performance expectancy. The moderating role of perceived severity and time pressure was found.